Efektivitas Perawatan Mulut Menggunakan Madu Terhadap Risiko Pneumonia Aspirasi Pada Pasien Stroke Yang Mengalami Penurunan Kesadaran Dan Disfagia - Dyah Untari; I made Kariasa; Muhammad Adam (JOURNAL EDUCATIONAL OF NURSING(JEN), 2019)
Aspiration pneumonia in patients with stroke can occur as a result of the gram-positive and gram-negative in the oral cavity that spreads to the respiratory tract of patients due to decreased ability to fight bacteria mouth. Selection of materials for oral care need to consider in terms of the material effectiveness, safety, convenience and cost efficiency. This quantitative study using a quasi-experimental design with pre and post test control group design. This research aims to study the effectiveness of oral care using honey to the risk of aspiration pneumonia in stroke patients who suffered loss of consciousness and dysphagia. In this design 46 respondents 23 respondents were divided into intervention group with oral treatments using honey and 23 respondents into a control group who received oral treatment with 0.2% chlorhexidine. Performed oral care performed by a nurse twice a day in the morning and evening for 30 minutes within 3 days sequentially. Results: There are significant relationships in oral care using honey to the risk of aspiration pneumonia in stroke patients who suffered loss of consciousness and dysphagia (p.0,000: α.0,05). The risk of aspiration pneumonia was lower by 2,522 with oral treatments using honey instead of using Clorhexidine 0.2%. Conclusion: Oral care using honey to effectively prevent the increased risk of aspiration pneumonia in pasein stroke decreased consciousness and dysphagia. Suggestion: Oral care with honey can be used as material for oral care, especially in the choice of antiseptic agent as proven in this study honey can maintain and even reduce the risk of aspiration pneumonia in stroke patients with loss of consciousness and dysphagia. This research can be a reference for subsequent research. Keywords: Chlorhexidine 0.2%, Honey, Oral Care, Stroke